Woman using Beckman Glucose Analyzer and BUN Analyzer - RAM Studio (1970)
An unidentified woman in a laboratory works in front of a bench holding a Beckman Glucose Analyzer and a Beckman BUN (Blood Urea Nitrogen) Analyzer. The Glucose Analyzer was developed by James Sternberg in 1969 and was one of several very successful medical testing and analysis instruments that Beckman Instruments produced in the 1970s. Its size, speed, and price enabled doctors to get fast, in-house results, instead of sending patients’ blood samples to a lab and awaiting a report.
Keywords: Women in science; Glucose--Analysis; Blood sugar--Analysis; Scientific apparatus and instruments; Beckman Instruments, Inc.; Medical laboratories--Equipment and supplies; Urea--Analysis; Employees; Women employees